Comparison of the kinematic patterns of kick between Brazilian and Japanese young soccer players - Pereira Santiago, Paulo Roberto; Palucci Vieira, Luiz Henrique; Barbieri, Fabio Augusto [UNESP]; Moura, Felipe Arruda; Exel Santana, Juliana; de Andrade, Vitor Luiz; de Souza Bedo, Bruno Luiz; Cunha, Sergio Augusto (Brieflands, 2016)
Background: Kicking performance is the most studied technical action in soccer and lower limbs kinematics is closely related to success in kicking, mainly because they are essential in imparting high velocity to the ball. Previous studies demonstrated that soccer leagues in different countries exhibit different physical demands and technical requirements during the matches. However, evidencewhether nationality has any influence in the kinematics of soccer-related skills has not yet been reported. The nationality of the players is an aspect that might be also relevant to the performance in kicking. Objectives: The aim of this study was to compare the lower limbs kinematic patterns during kicking, between Brazilian and Japanese young top soccer players. Patients and Methods: Seven Brazilian (GA) and seven Japanese (GB) U-17 players performed 15 side-foot kicks each, with a distance of 20 m away from the goal, aiming a target of 1 × 1 m in upper corner, constrained by a defensive wall (1.8 × 2 m). Four digital video cameras (120 Hz) recorded the performance for further 3D reconstruction of thigh, shank and foot segments of both kicking and support limbs. The selected kicking cycle was characterized by the toe-off of the kicking limb to the end of the kicking foot when it came in contact with the ball. Stereographical projection of each segment was applied to obtain the representative curves of kicking as function of time for each participant in each trial. Cluster analysis was performed to identify the mean GA and GB curves for each segment. Silhouette coefficient (SC) was calculated, in order to determine the degree of separation between the two groups’ curves. Results: Comparison between the median confidence intervals of the SC showed no differences between groups as regards lower limb patterns of movements. Task accuracy was determined by the relative frequency that the ball reached the target for all attempts and no differences were found (GA: 10.48 ± 14.33%; GB: 9.52 ± 6.51%; P = 0.88). Conclusions: We conclude that lower limb kinematic patterns, in support and ball contact phases, are similar in young Brazilian and Japanese soccer players during free kicks when adopting the side-foot kick style.
Keywords: Biomechanics; Cluster analysis; Kicking; Nationality; Soccer